Kajian Resep Obat Batuk Anak Di Salah Satu Apotek Di Kota Batam Periode Januari - Desember 2022 - Reny Haryani; Rastria Meilanda; Lailatul Khasanah Setyowardani (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2023)
Prescription review is an assessment of prescription writing by pharmacy staff involve administrative aspect, pharmaceutical aspect and clinical aspect. Prescription review is fundamental aspect to avoids medication errors. This study aims to determine the suitability of prescriptions for children's cough medicine at one of the pharmacies in Batam period January-December 2022 with Minister of Health Regulation No. 73 of 2016. Category of research is non-experimental research with descriptive which data collection using simple random sampling technique. The results of the study showed that completeness of administrative aspect on prescriptions were patient's name 100%, age 100%, gender 0%, weight 0%, doctor's name 100%, Practice Lisences Number 51%. Completeness of pharmaceutical aspect involve dosage strength 1%, route of administration 100%, compatibility 100%. And the clinical suitability of drug interactions is 94%, drug dosage is 88%, no adverse drug reaction (ADR) and allergies are 100%, contraindications are 100%.